2014
DOI: 10.1111/ijcs.12095
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of organic food purchase intentions in mainland China – evaluating potential customers' attitudes, demographics and segmentation

Abstract: This research aims to investigate the important attitudes, demographics and segmentation of potential consumers' purchase intentions of organic food in urban China. The survey instrument was designed based on validated measures and three focus group interviews. Data were collected at supermarkets in the major cities which yielded 935 usable responses. The 23 attributes that measured attitudes were factor analysed and five dimensions were generated. Of these, the strongest dimension was 'Certification' which ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 58 publications
11
86
1
9
Order By: Relevance
“…These results are consistent with those found in several other studies in which the largest proportion of consumers of organic food found in street and organic markets are women (Çabuk et al, 2014;Chen et al, 2014;Mohamada et al, 2014;Van Loo et al, 2014;Wu et al, 2014).…”
Section: Analysis Of the Socioeconomic Characteristics Of Each Groupsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with those found in several other studies in which the largest proportion of consumers of organic food found in street and organic markets are women (Çabuk et al, 2014;Chen et al, 2014;Mohamada et al, 2014;Van Loo et al, 2014;Wu et al, 2014).…”
Section: Analysis Of the Socioeconomic Characteristics Of Each Groupsupporting
confidence: 93%
“…The name of this group was chosen because these consumers have the lowest scores for most factors in relation to the other groups. Chen et al (2014) identified different groups of consumers and named them as: "Consumers aware of safety"; this type of consumers are interested in certifications, coinciding with the "Conscious consumers interested in certifications"; "Gastronomic consumers"; this group pays attention to the country of origin of the products, something that was not included in the questionnaires used in this work; and "Skeptical consumers", which have a similar behaviour to the "Unconscious opportunistic consumers", but differ in that sceptical consumers attach the greatest importance to social status. Tsourgiannis et al (2015) identified other groups: "Curious consumers", who consume organic wine just for prestige and curiosity; "Opportunistic consumers" who are not influenced by any particular factor, and are very similar to the "Unconscious opportunistic consumers"; and "Conscious consumers", who are interested in buying these products because they are free of additives, do not damage the environment and have nutritional value, coinciding with the first two groups identified in this work.…”
Section: Consumer Of Food Products In Organic Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is focused on the researches that purchase of organic foods can be seen as an action motivated by beliefs about healthiness, about animal welfare and food safety, about the environmental care, and about the way the product is produced. (Chen et al, 2014;Çabuk et al, 2014;Mohamad et al, 2014;Manuela et al, 2013;Sangkumchalian and Huang, 2012;Shafie and Rennie, 2012;Hjelmar, 2011;Maya et al, 2011;Michaelidou and Hassan, 2010;Zander and Hamm, 2010;Arvola et al, 2008;Gracia and Magistris, 2008;Schobesberger et al, 2008;Wadoloswka et al, 2008). Additionally, a growing interest in organic food has prompted many studies comparing aspects of organic food because other sensory attributes such as nutritive value, taste, freshness and appearance also affect consumer preference (Probst et al, 2012;Hjelmar, 2011;Michaelidou and Hassan, 2010;Alizadeh et al, 2008;Wier et al, 2008;Kihlberg and Risvik, 2007).…”
Section: Introductionmentioning
confidence: 99%